Performance of a Micro-Scale Membrane Reactor for Greywater Treatment at Household Level - Vasileios Diamantis (Membranes, 2021)
An aerated membrane reactor (25 L working volume) equipped with 1.5 m2 hollow-fiber module was designed and operated using synthetic greywater for household water reuse. Activated sludge (MBR), activated carbon (PAC), zeolite (ZEO) and iron hydroxide (GEH) were added in separate experiments to optimize membrane hydraulic performance and removal efficiency of organics. The use of additives improved permeate quality (in terms of Chemical Oxygen Demand—COD) compared to the direct membrane filtration mode of operation. GEH and MBR were efficient for phosphorus removal, which was not the case for PAC and ZEO. No significant improvement of membrane flux was recorded when PAC, ZEO or GEH were added inside the membrane tank. The MBR system displayed optimum performance during medium-term operation, with COD removal efficiency 85% and permeate flux between 40 and 25 L m−2 h−1. The capital costs of the proposed technology were around 300 € and the operational costs below 80 € yr−1, rendering the process feasible at household level. Greywater treatment systems for household applications are still on their infancy; however, this trend is expected to change due public perception towards circular economy, water conservation and reuse.